DESKRIPSI SOAL UJIAN NASIONAL MATEMATIKA SMA TAHUN PELAJARAN 2018/2019 BERDASARKAN TAKSONOMI SOLO - Dwi Lestari; Budiyono ,; Dita Yuzianah (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
This study aims to describe the level of the national high school science exam questions for the 2018/2019 school year, which is defined based on the SOLO taxonomy and examines what operational verbs are in the subject. This type of research uses descriptive qualitative. The source of this research is the text of the National High School science Mathematics national examination for 2018/2019 academic year. The data collection technique used is the data analysis technique, according to Milles and Huberman. The object retrieval technique used is using a comparative method. The question used in this study were 20 odd number questions on the text of the Mathematics science high school national exam. The results of this study are as follows. The level questions on the national mathematics high school mathematics national exam 2018/2019 includes four levels in the SOLO taxonomy with uni structural breakdown of 5%, multi structural 10%, relational by 75%, and extended abstracts by 10%.